Higher harmonic generation of Rayleigh wave at debondings in FRP-retrofitted concrete structures. (19th September 2018) - Mohseni, H; Ng, C T
Abstract: The use of ultrasonic nonlinearity for damage detection and monitoring of structures has attracted growing attention. Interaction of guided waves with contact-type damage, such as debonding, is one of the major sources of ultrasonic nonlinearity. This paper investigates higher harmonic generation of Rayleigh waves in FRP-retrofitted concrete structures due to debonding between FRP and concrete. In this study, propagation and scattering of Rayleigh wave are simulated using a three-dimensional finite element model. The numerical simulations of both linear and nonlinear Rayleigh wave are validated with experimentally measured data. There is very good agreement between numerical and experimental results. This paper also investigates the scattering directivity patterns of second and third harmonics of Rayleigh wave. The results provide physical insights into nonlinear Rayleigh wave generated by debonding between FRP and concrete. Overall, the findings of this study can further advance the damage detection methods using the nonlinear Rayleigh wave.